Project work and development of children’s competencies in kindergarten : the Croatian experience - Slunjski, Edita (Array, 2013)
The project represents a form of an integrated curriculum based on the affirmation of children’s curiosity and on encouraging their experiential and self-motivated learning. Adequate organisational assumptions i.e. learning infrastructures should be formed in a kindergarten in order to comprehend the good quality projects which are suitable for development of competency in children. A kindergarten is thought to be a place of “walk to discovery”, a place of collaboration, unity and tolerance, a place of democratic living, active participation and co-deciding of children and adults. Continuous professional improvement of educators and other employees of a kindergarten as an institution must be ensured in order to comprehend which projects are of high quality, this is aimed at development of children's research and reflexive skills. Special attention is drawn to sophisticated roles of educators in shaping the project, which moves away from any form of manipulation over children and their activities. Joint planning of educators, joint realisation and joint evaluation of the project activities represent a strong foothold for shaping the project and development of children’s competencies. By joint consideration and coordinated actions during different activities, the educators create a space for critical discussion on different segments of the project, thus being a precondition of its development and assurance of its quality. In that sense, we have done action research with a final goal of better understanding and advancement of conditions for which we think favours to the development of projects in institutions of early development. We have especially concentrated on: 1. Organisation of a space - material surroundings as an preliminary condition to the development of the project 2. The role of the educator in achievement of children activities on the project 3. Various forms of documentation that contributes to the development of the projects. In this work, we would display insights that we have got to as well as show examples of quality projects that were developed in that period of time.